Autonomous Orientation Behaviors Influence Towards Ex-Juvenile Entrepreneurs Delinquent Behavioral Change in Katsina State, Nigeria : A Conceptual Paper - Usman, Bilyaminu; Hashim, Sharizal; Lamptey, Jeff; Ashemi, Baba Ali (MJSSH Publisher, 2020)
Recent Entrepreneurship orientation autonomous dimension discussion revealed the important and the positive influence of autonomous orientation as one of the Entrepreneurial orientations (EO) towards organizational performance and profitability. However, discussion of autonomous orientation in the context of individual such as entrepreneurs behavioral change impact still silent, especially in the context of ex-juvenile entrepreneur that can give an insight to the Entrepreneurship body of knowledge. Therefore, the objective of this conceptual paper is to understand the influence of autonomous orientation behaviors as one of the individual entrepreneurial orientation (IEO) towards delinquent behavioral change of ex-juvenile entrepreneurs. The conceptual paper proposed the framework that exjuvenile entrepreneurs could be autonomous and more importantly autonomous orientation might have a positive influence towards ex-juvenile entrepreneurs’ delinquent behavioral change. Subsequently relating development of this concept, the conceptual review demonstrates the importance of the autonomous orientation as an effective deliberate orientation for ex-juvenile entrepreneurs once they reconsider their delinquent behavior with entrepreneurial autonomous activities. Assuming autonomous orientation looks to replicate a desired reconciliation amongst delinquent behaviors and entrepreneurial autonomous orientation as an alternative to delinquency. Lastly, the conceptual paper concludes with suggesting some inferences for future research to dig out the study theoretically, conceptually and empirically of the individual EO autonomous orientation behaviors among delinquent populace (exjuvenile entrepreneurs) context. This conceptual paper provides a fresh knowledge about the IEO autonomous orientation potentiality in the entrepreneurs’ self-development and an insight to the entrepreneurship framework.